The Fight Against Corruption in Vietnam: The Role of Online Press - Thanh Huyen, Nguyen (VNU Journal of Science: Policy and Management Studies, 2020)
The epidemic of corruption could derail sustainable development of any country, and Vietnam is no exception. From 2016, Vietnamese government had been taking a variety of anti-corruption policies to tackle corruption issues, of which empowering the role of online press has made notable progress in the last few years. This paper briefly reviewed the legal framework on corruption prevention and examined how online press takes part in curbing corruption and its influence on the fight against corruption in Vietnam. The results show that the online press played a significant role in curbing corruption by being a powerful tool for propaganda as well as an active channel to report about corruption in Vietnam from 2016 to 2019. However, there are still many challenges to overcome in order to strengthen the role of online press in fighting corruption in Vietnam.